Desmoplastic hybrid ameloblastoma presenting as a fibrous epulis - L R Kumaraswamy Naik; Pushparaja Shetty; Padmaraj Hegde (Wolters Kluwer Medknow Publications, 2014)
Desmoplastic ameloblastoma (DA) is a rare variant of ameloblastoma with specific clinical, imaging, and histological features. Histologically, it is characterized by extensive stromal desmoplasia with small compressed nests and strands of odontogenic epithelium. The purpose of this article is to present a case of central DA that showed unusual clinical presentation of a classic solid/multicystic ameloblastoma occurring as a peripheral lesion in the form of gingival epulis, arising from extraction site and showed histopathological feature of a hybrid variant.